SSHLDA: A semi-supervised hierarchical topic model - Mao, X.-L. (2014)
EMNLP-CoNLL 2012 - 2012 Joint Conference on Empirical Methods in Natural Language Processing and Computational Natural Language Learning, Proceedings of the Conference